Peningkatan Kualitas Pelayanan Keperawatan Melalui Interdisciplinary Rounds - Dilgu Meri; Fitra Mayenti; Arya Ramadia (Abdimas Universal, 2022)
Sansani Pekanbaru is a hospital located on Jl. Soekarno Hatta No. 501, Air Hitam Kec. Payung Sekaki, Pekanbaru City.. Along with the times, Sansani Hospital is required to be able to provide quality services. Quality nursing care is what patients want. One of the efforts to improve the quality of service is through the implementation of the Interdisciplinary Bedside Round which is part of the nursing round. In implementing this program, the proposing team has prepared a method plan that was carried out during the process. The training activities use counseling methods, role play, and mentoring. The results showed that the mean of knowledge before being given training was 6.33 (SD 0.500) and the mean of knowledge after being given training was 6.78 (SD 0.441). The results of the bivariate analysis showed a p value of 0.035 (0.05) which means that there was a significant effect before and after training.